Micromanaging aerobic respiration and glycolysis in cancer cells - Ayla V. Orang; Janni Petersen; Ross A. McKinnon; Michael Z. Michael (Elsevier, 2019)
Background: Cancer cells possess a common metabolic phenotype, rewiring their metabolic pathways from mitochondrial oxidative phosphorylation to aerobic glycolysis and anabolic circuits, to support the energetic and biosynthetic requirements of continuous proliferation and migration. While, over the past decade, molecular and cellular studies have clearly highlighted the association of oncogenes and tumor suppressors with cancer-associated glycolysis, more recent attention has focused on the role of microRNAs (miRNAs) in mediating this metabolic shift. Accumulating studies have connected aberrant expression of miRNAs with direct and indirect regulation of aerobic glycolysis and associated pathways. Scope of review: This review discusses the underlying mechanisms of metabolic reprogramming in cancer cells and provides arguments that the earlier paradigm of cancer glycolysis needs to be updated to a broader concept, which involves interconnecting biological pathways that include miRNA-mediated regulation of metabolism. For these reasons and in light of recent knowledge, we illustrate the relationships between metabolic pathways in cancer cells. We further summarize our current understanding of the interplay between miRNAs and these metabolic pathways. This review aims to highlight important metabolism-associated molecular components in the hunt for selective preventive and therapeutic treatments. Major conclusions: Metabolism in cancer cells is influenced by driver mutations but is also regulated by posttranscriptional gene silencing. Understanding the nuanced regulation of gene expression in these cells and distinguishing rapid cellular responses from chronic adaptive mechanisms provides a basis for rational drug design and novel therapeutic strategies. Keywords: Metabolism, Warburg effect, microRNA, Aerobic glycolysis, Cancer